2022
DOI: 10.1007/s11130-022-00983-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Properties of Selected Fruit Juices

Abstract: Fruit and fruit juices are a valuable source of bioactive compounds, which can protect our organisms from oxidative stress. The phenolic compounds and other phytochemicals may affect the antimicrobial properties of juices. The aim of this study has been to evaluate antioxidant and antimicrobial properties of selected berry juices and vitamin C-rich fruit juices. The research material was composed of seven juices, including three from berries (elderberry chokeberry, cranberry), three from vitamin C-rich fruit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
1
23
2
Order By: Relevance
“…As in TPC, the extrusion process did not generate significant changes in the TF content of UB10 and EB10 (5.37 and 5.85 mg QE/100 mL of beverage) ( p < 0.05). These values are similar to those reported by Nowak et al [ 52 ] for the juice of different fruits (0.024 a 5.607 mg QE/100 mL). Elhanafi et al [ 20 ] reported lower values than those observed in this study for beige sesame (10 mg QE/100 g).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As in TPC, the extrusion process did not generate significant changes in the TF content of UB10 and EB10 (5.37 and 5.85 mg QE/100 mL of beverage) ( p < 0.05). These values are similar to those reported by Nowak et al [ 52 ] for the juice of different fruits (0.024 a 5.607 mg QE/100 mL). Elhanafi et al [ 20 ] reported lower values than those observed in this study for beige sesame (10 mg QE/100 g).…”
Section: Resultssupporting
confidence: 91%
“…The TPC values for UB10 and EB10 were 14.90 and 15.97 mg GAE/mL g of beverage. These values are higher than those observed by Nowak et al [ 52 ] for the juice of elderberry, chokeberry, cranberry, wild rose, Japanese quince, sea buckthorn, and noni (6.82, 11.26, 2.77, 16.61, 11.08, 4.70, 3.00 mg GAE/100 mL). The TPC are lower than those reported by Behnam Nik and Vazifedoost [ 53 ] for a functional beverage of Securigera securidaca extract beverage (200 a 550 mg GAE/100 mL); this is partly due to the compounds used in the formulation of the beverage (Stevia, Honey, Apple Juice, citric acid, and mint) that by themselves contribute to TPC.…”
Section: Resultscontrasting
confidence: 60%
“…These substances consist of bioactive compounds such as carotenoids, sterols, phenolic compounds (including flavonoids and non-flavonoids), and dietary fiber [ 4 ]. Recent studies have provided valuable insights into the potential health-promoting effects of bioactive compounds present in fruits and FBP: anti-aging [ 5 ], antioxidant [ 6 , 7 ], anticancer [ 8 , 9 ], antiproliferative, anti-neurodegenerative, anti-inflammatory [ 10 ], antidiabetic [ 11 , 12 ], antimicrobial [ 9 , 13 , 14 ], anti-inflammatory [ 15 , 16 ], hepatoprotective [ 17 , 18 ], and neuroprotective [ 8 , 19 ] ( Figure 1 ). These beneficial properties of fruits can make them valuable ingredients in the production of functional food products such as shortbread cookies.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules 2023, 28, x FOR PEER REVIEW 2 of 28 antiproliferative, anti-neurodegenerative, anti-inflammatory [10], antidiabetic [11,12], antimicrobial [9,13,14], anti-inflammatory [15,16], hepatoprotective [17,18], and neuroprotective [8,19] (Figure 1). These beneficial properties of fruits can make them valuable ingredients in the production of functional food products such as shortbread cookies.…”
Section: Introductionmentioning
confidence: 99%
“…Although all coated samples were extracted in the same way, higher antimicrobial activity observed in quince slices coated with CaCl 2 + pectin and dried with microwave might be due to the effects of phenolics that were better preserved with this drying method. In several studies (Fattouch et al, 2007;Gamaleldin et al, 2014;Nowak et al, 2022;Urbanaviciute et al, 2020), close results were reported for antimicrobial activities; however, various extracts of quince in above cited studies were reported to have better antimicrobial activity against S. aureus than E. coli.…”
Section: Comparison Of Different Drying Techniquesmentioning
confidence: 86%